1989
DOI: 10.1172/jci114323
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated beef insulin treatment elicits CD8+ T cells that may abrogate immunologic insulin resistance in type I diabetes.

Abstract: The in vitro responses of T cells from 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…1C Lower). Rather, some DC/M4 peptides consist of C-terminal A-chain residues A20 and A21 disulfide-linked to core B-chain residues, and such peptides are not immunogenic (4,22 2A). This peak was absent from precipitated DC/MO samples (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C Lower). Rather, some DC/M4 peptides consist of C-terminal A-chain residues A20 and A21 disulfide-linked to core B-chain residues, and such peptides are not immunogenic (4,22 2A). This peak was absent from precipitated DC/MO samples (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that heterodimeric disulfidelinked insulin peptides are presented by B cells to CD4+ T cells in vitro (4)(5)(6). Since this suggested that a disulfide-linked peptide binds to MHC class II, we analyzed whether human insulin (HI) is processed into a disulfide-linked peptide that binds to MHC class II in vivo.…”
mentioning
confidence: 99%
“…Insulin and proinsulin are targets of autoantibodies (13)(14)(15) and T cells (16)(17)(18)(19)(20)(21)(22)(23) in diabetic and prediabetic subjects. Anti-insulin antibodies are the first autoantibodies detected in children at risk for diabetes (15).…”
mentioning
confidence: 99%
“…Because of this close homology, thymic IGF-2 would be a good candidate for inducing central immune self-tolerance of the whole insulin family although the tolerance to insulin per se would be weaker. This again might explain why B-and Tcell autoreactivity to insulin has been equally observed in diabetic and related non-diabetic individuals [33].…”
Section: Central Self-tolerance Of the Insulin Familymentioning
confidence: 93%
“…This is indirectly reflected by the frequency and titer of antibodies obtained after active immunization with the three peptides [32]. In the same line of reasoning, the high occurrence of anti-insulin autoantibodies in the normal population [33] could be linked to the low level of INS expression within the human thymus. The IGF-2 protein contains peptide sequences that have been highly conserved throughout evolution of the insulin family.…”
Section: Central Self-tolerance Of the Insulin Familymentioning
confidence: 95%